Dysmenorrhoea and its association with stress among nursing students of a selected medical college: A cross-sectional study - Thapa, Babita; Regmi, Kalpana; Shrestha, Nira; Shrestha, Muna (Journal of Kathmandu Medical College, 2023)
Background: Dysmenorrhoea is a painful menstruation often presented with other symptoms such as sweating, headache, nausea, vomiting, and diarrhoea which influence the quality of life and social activities among the undergraduate students. Psychological disorders like stress, anxiety and depression have bi-directional relationship with dysmenorrhoea. Objectives: To assess the prevalence of dysmenorrhoea and its association with stress among nursing students of a selected medical college. Methods: Analytical cross-sectional study was conducted among nursing students of NAIHS-CON from 2021 August 26 to 2021 September 2 after institutional ethical clearance. Total 154 nursing students were included in the study using proportionate stratified simple random sampling technique by lottery method. Data were collected using a semi-structured, self-administered questionnaire using Perceived Stress Scale (PSS). The collected data were analysed using SPSS software v.20. Results: The study findings revealed that 131 (85.1%) of the nursing students had moderate perceived stress level and 14 (9.1%) of them had mild stress level. The mean perceived stress score with standard deviation was 19.27 ± 4.806. The findings of the study revealed that 115 (74.7%) of the nursing students had dysmenorrhoea. Dysmenorrhoea was found to be significantly associated with family history of dysmenorrhoea (p <0.001) and pattern of menstrual cycle (p = 0.04). Conclusion: Most of the nursing students experience dysmenorrhoea which might result in psychological stress and bring negative effects on their physical health. As a result, it may impact on their academic performance. Therefore, it is important to enhance awareness regarding dysmenorrhoea to reduce physical and mental problems.